2000
DOI: 10.1292/jvms.62.583
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in vivo Administration of Anti-IL-10 or Anti-IFN-.GAMMA. Monoclonal Antibody on the Host Defense Mechanism against Plasmodium yoelii yoelii Infection.

Abstract: ABSTRACT. Our previous reports indicated that C57BL/6 mice infected with a lethal variant of Plasmodium yoelii 17X (P. yoelii 17XL) produced high levels of interleukin 10 (IL-10) and interferon-γ (IFN-γ) while mice infected with the nonlethal variant of the parasite did not produce detectable levels of IL-10. In the present study, the involvement of IL-10 and IFN-γ in exacerbation or regulation of bloodstage malaria was investigated by using the lethal variant of P. yoelii 17XL and monoclonal antibodies (mAb) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 16 publications
1
38
2
Order By: Relevance
“…Despite clear evidence that anti-inflammatory cytokines and/or regulatory T cells inhibit the clearance of PyL pRBC (15,16,21,22,35,36), this study has not shown any role for T cells, NK cells, or IFN-␥ in the control of acute P. yoelii infection. However, given the absence of MHC expression on the majority of red blood cells (19), it is probable that neither T cells nor NK cells play the terminal effector role in parasite killing.…”
Section: Vol 75 2007 Control Of Lethal and Nonlethal P Yoelii Infecontrasting
confidence: 80%
See 3 more Smart Citations
“…Despite clear evidence that anti-inflammatory cytokines and/or regulatory T cells inhibit the clearance of PyL pRBC (15,16,21,22,35,36), this study has not shown any role for T cells, NK cells, or IFN-␥ in the control of acute P. yoelii infection. However, given the absence of MHC expression on the majority of red blood cells (19), it is probable that neither T cells nor NK cells play the terminal effector role in parasite killing.…”
Section: Vol 75 2007 Control Of Lethal and Nonlethal P Yoelii Infecontrasting
confidence: 80%
“…In contrast, IFN-␥ Ϫ/Ϫ mice on a C57BL/6 ϫ 129 background were unable to clear PyNL infections (56). Moreover, recombinant IFN-␥ protected SW, BALB/c, and CBA mice against PyL infection (47), and mice treated with anti-IFN-␥ antibodies succumbed earlier to lethal P. yoelii infection but had parasite levels similar to those of control mice (21). These results suggest that the lack of an early NK/IFN-␥ response in PyL-infected mice may impair parasite control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial pro-inflammatory response may switch to a predominant anti-inflammatory response that is mediated by immunoregulatory cytokines, such as TGF-β and IL-10 which down-regulate proinflammatory cytokine production to avoid malaria-associated pathology (7)(8)(9)(10)(11)(12). The pro-and anti-inflammatory cytokine balance is critical in determining the outcome of malaria infection (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%